Sonographic findings in two cases of lymphangioma of the mesocolon in adults. Issue 1 (25th April 2017) - Naganuma, Hiroko; Ishida, Hideaki; Komatsuda, Tomoya; Hakamada, Mayu; Sawada, Toshiya; Satoyoshi, Rika; Enomoto, Katsuhiko; Miyauchi, Takaharu
ABSTRACT: Lymphangioma of the mesocolon is very rare. We report two cases of surgically resected and histologically proven mesocolic lymphangioma in adults. In both cases, ultrasound revealed a large cystic mass with multiple thin septa in the lower abdomen. A peculiar finding was the large craniocaudal sliding movement of the mass synchronized with the patient's respiration, which was a clue to the diagnosis of mesenteric lymphangioma. © 2017 Wiley Periodicals, Inc. J Clin Ultrasound 46 :78–81, 2018;